Penggunaan Media Audiovisual Untuk Menanggulangi Perilaku Bullying Siswa Di Smp Negeri 23 Pekanbaru - Sindi Ayudia Pama; Fitra Herlinda (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
It was Pre-experimental research with the one group pretest and posttest design. It aimed at overcoming student bullying behavior at State Junior High School 23 Pekanbaru in the academic year of 2018/2019. 360 students were the population. The subjects of this research were 40 students that were the samples, and the samples were selected from a part of the population. Likert scale was the instrument. Validity test was done by using SPSS for Windows release 21.00. The data were analyzed by using paired sample t-test. The research findings showed that overcoming student bullying behavior before being given audiovisual media on informational service was on medium category and the mean was 72.37. after giving a treatment, it increased to high category and the mean was 81.17. So, it could be stated that there was a difference between pretest and posttest. It could be concluded that audiovisual media on informational service was effective in overcoming student bullying behavior and it could be seen from the data analysis result that tobserved 3.321 was higher than ttable 2.02, so H0 was rejected..